From black clouds to black holes - Narlikar, Jayant V. (Singapore World Scientific, 2012)
This book introduces the fascinating world of astrophysics and cosmology, tracing the evolution of ideas from interstellar clouds to the formation of black holes. Written in accessible language, it offers insights into stellar evolution, relativity, and the mysteries of the universe.
Includes bibliographical references and index
Keywords: Cơ bản - Vật lý